2014
DOI: 10.1037/a0033489
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for color and shape: When is the gaze guided by feature relationships, when by feature values?

Abstract: One of the most widespread views in vision research is that top-down control over visual selection is achieved by tuning attention to a particular feature value (e.g., red/yellow). Contrary to this view, previous spatial cueing studies showed that attention can be tuned to relative features of a search target (e.g., redder): An irrelevant distractor (cue) captured attention when it had the same relative color as the target (e.g., redder), and failed to capture when it had a different relative color, regardless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
103
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(122 citation statements)
references
References 106 publications
18
103
1
Order By: Relevance
“…This suggests that when contexts render visual search relatively robust against repeated distraction by salient stimuli, a repetition of the distracting feature does not further decrease attentional capture and thus does not further improve search performance. In line with this, it was previously found in an eye-tracking study that repeating an irrelevant distractor color did not alter saccade trajectories in a homogeneous context when color changes were unpredictable (Becker et al, 2014). Search displays with heterogeneous contexts, however, can benefit from repetition of an irrelevant distractor feature, but only if the color is systematically varying.…”
Section: Mechanisms Of Distractor-intertrial Primingsupporting
confidence: 57%
“…This suggests that when contexts render visual search relatively robust against repeated distraction by salient stimuli, a repetition of the distracting feature does not further decrease attentional capture and thus does not further improve search performance. In line with this, it was previously found in an eye-tracking study that repeating an irrelevant distractor color did not alter saccade trajectories in a homogeneous context when color changes were unpredictable (Becker et al, 2014). Search displays with heterogeneous contexts, however, can benefit from repetition of an irrelevant distractor feature, but only if the color is systematically varying.…”
Section: Mechanisms Of Distractor-intertrial Primingsupporting
confidence: 57%
“…According to the relational account, the failure to obtain more evidence for the orange channel in this and other experiments is due to the fact that there is a strong preference in the visual system to bias visual selection to the relative color of the target instead of its physical color (e.g., Becker, 2010a; Becker et al, 2013, 2014; Harris et al, 2013). With this, the relational account seems to provide a better explanation for present and past results, because it avoids the need to constantly re-define the number of channels and their bandwidth so that they match the results.…”
Section: Discussionmentioning
confidence: 60%
“…This holds because, in the absence of a dedicated orange channel, the red and yellow non-targets would produce higher activations in the red and yellow channels than the orange target, so that the orange target could not be located pre-attentively (e.g., Wolfe, 1994). In contrast to this prediction, it has been shown that an orange item can be successfully located among red and yellow non-targets (e.g., Bauer et al, 1995; Harris et al, 2013; Becker et al, 2014). In fact, Becker et al (2013) showed that a briefly presented orange cue among two red and two yellow other cues can involuntarily capture attention, showing that orange is pre-attentively localizable among red and yellow.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, studies testing the relational account against a feature‐specific view confirmed that capture depends on the feature relationships of the target and distractor rather than their absolute feature values (e.g., Becker et al., , ). In one study, the Ludwig and Gilchrist () paradigm was used, but the number of distractor features was increased to test whether attention was indeed biased to the target feature value (Becker, Harris, Venini & Retell, in press). In one block, observers had to make a fast eye movement to an orange target that was embedded among three gold (yellow‐orange) non‐targets.…”
Section: Evidence For the Relational Accountmentioning
confidence: 99%